Developing a Marketing Strategy Based on Swot Analysis to Increase PT.XY's Competitiveness - Arisana, Vina (Siber International Journal of Education Technology (SIJET), 2024)
This research aims to identify the strengths, weaknesses, opportunities, and threats faced by PT.XY in the information and entertainment industry in Indonesia through SWOT analysis, and develop effective marketing strategies to improve the company's competitiveness. The research method used is a qualitative and quantitative approach with a combination of mixed methods. The results showed that PT.XY has strengths in commitment to information security and multi-channel services, but faces weaknesses in dependence on technology and limited resources. Opportunities in the growth of the entertainment industry and the use of digital technology should be capitalized on, while threats from fierce competition and changes in the global economy need to be anticipated. The proposed marketing strategy includes diversification of products and services, adoption of advanced technology, and improvement of service quality. The implementation of these strategies is expected to improve PT.XY's competitiveness and maintain its position in the competitive market.